Getting more from standard rotator cuff strengthening exercises. (June 2020) - Ganderton, C; Kinsella, R; Watson, L; Pizzari, T
Background: A simple modification to standard rotator cuff exercises using an additional resistance band around the scapula has been recommended in the clinical setting, postulated to encourage activation of the posterior scapular stabilisers and increase rotator cuff activation. The aim of this clinical laboratory study was to compare scapular and rotator cuff muscle activation between standard and modified exercises. Methods: Electromyographic data were collected from 10 healthy adults via surface and intramuscular electrodes from the scapular and rotator cuff muscles. Internal and external rotation exercises of the shoulder with the arm abducted to 0°, 45° and 90° were performed using one handheld resistance band (standard) or two bands with the additional band applied to the scapula (modified). Results: Activation of the trapezii and rhomboid muscles during the modified exercises at 0° and 45° of abduction was significantly greater when compared to the standard exercises ( P  < 0.05). No significant differences were found in rotator cuff muscle activation. Discussion: Applying resistance to the posterior scapula increases activation of some scapular stabilising muscles particularly in lower ranges of abduction. This study provides preliminary evidence that this simple modification can elicit greater scapular muscle activity, potentially producing enhanced exercise outcomes with minimal additional effort.